Diversity in mRNA expression of the serine-type carboxypeptidase ocpG in Aspergillus oryzae through intron retention. Issue 8 (3rd August 2014) - Ishida, Ken; Kuboshima, Megumi; Morita, Hiroto; Maeda, Hiroshi; Okamoto, Ayako; Takeuchi, Michio; Yamagata, Youhei
Abstract: Alternative splicing is thought to be a means for diversification of products by mRNA modification. Although some intron retentions are predicted by transcriptome analysis in Aspergillus oryzae, its physiological significance remains unknown. We found that intron retention occurred occasionally in the serine-type carboxypeptidase gene, ocpG . Analysis under various culture conditions revealed that extracellular nitrogen conditions influence splicing patterns; this suggested that there might be a correlation between splicing efficiency and the necessity of OcpG activity for obtaining a nitrogen source. Since further analysis showed that splicing occurred independently in each intron, we constructed ocpG intron-exchanging strain by interchanging the positions of intron-1 and intron-2. The splicing pattern indicated the probability that ocpG intron retention was affected by the secondary structures of intronic mRNA. Graphical abstract: : The nitrogen source of the culture medium altered the alternative splicing pattern of serine-type carboxypeptidase ocpG mRNA in Aspergillus oryzae.